Maritime Climate in the Canary Islands and its Implications for the Construction of Coastal Infrastructures - Jesica Rodríguez-Martín; Noelia Cruz-Pérez; Juan C. Santamarta (Salehan Institute of Higher Education, 2022)
Islands are isolated systems that depend on maritime trade for their subsistence. Efficient, durable and structurally reliable port infrastructures are essential for the economic and social development of islands. However, not all port infrastructures are designed in the same way. They can vary, depending on whether they are built on continental land, built on non-volcanic islands or built on volcanic oceanic islands (such as the Canary Islands, Spain). The latter islands are the subject of this study due to their specific features, construction difficulties and the importance of sound maritime infrastructures. The maritime climate of an area consists of the wave and storm regimes that affect it and, from these, the coastal dynamics and coastal formations of that area can be studied. For this reason, historical data were collated on significant directional wave heights from 1958 to 2015 from several WANA-SIMAR points in the virtual buoy network of State Ports of Spain located near the Canary Islands. These data have been studied to obtain the maximum directional wave heights (Hs) at each point. With this analysis, we have obtained useful summary tables to calculate wave height by a graphic method that transforms the distribution function into a line drawn on probabilistic paper, using reduced variables. This enables adjustments to be made by linear regression and minimum square methods to facilitate planning and design of maritime infrastructures in a reliable way. Doi: 10.28991/CEJ-2022-08-01-02 Full Text: PDF